Determinan Pertumbuhan Ekonomi Ditinjau dari Pendapatan Daerah dan Tingkat Kemandirian Daerah - Ayu, Putri Puspita; Septiani, Tika (Jurnal Kajian Akuntansi, 2019)
Declining economic growth rate in West Java province for the last six years (2012-2016) resulted in the purchasing power of low society. This situation led to the weakening of economic activity in West Java province during this period, so it is necessary to do efforts to stimulate related parties especially the provincial government of West Java to be more centered on local economic empowerment to increase its regional revenues. This condition will have an impact on increasing economic growth. The purpose of this article was intended to examine the influence of indigenous revenue, transfer income, other legitimate revenues and the level of regional independence to economic growth in the province of West Java. This study uses a method of verificative. The population in this study was all the local governments of the regency and city of West Java in 2012-2017 and obtained 162 samples of research data consisting of 1 province, 26 districts and cities. The data analysis techniques in this study used multiple regression analyses. Based on the results of regression analysis showed that the economic growth rate of the district and the city of West Java province was significantly influenced by the regional original revenue (PAD), transfer income, other legitimate income, and the level of Regional independence.Keyword: Economic growth; Local revenue; Transfer income; Other legitimate revenues; Level of independence Abstrak Menurunnya laju pertumbuhan ekonomi di Provinsi Jawa Barat selama enam tahun terakhir (2012-2016) menghasilkan daya beli masyarakat yang rendah. Situasi ini menyebabkan melemahnya kegiatan ekonomi di Provinsi Jawa Barat dalam kurun waktu tersebut, sehingga perlu dilakukan upaya menstimulasi pihak terkait khususnya pemerintah provinsi Jawa Barat agar lebih terpusat pada pemberdayaan ekonomi lokal untuk meningkatkan pendapatan daerahnya. Kondisi tersebut akan berdampak pada peningkatan pertumbuhan ekonomi. Tujuan artikel ini dimaksudkan untuk menguji pengaruh pendapatan asli daerah, pendapatan transfer, lain-lain pendapatan yang sah dan tingkat kemandirian daerah terhadap tingkat pertumbuhan ekonomi di Provinsi Jawa Barat. Studi ini menggunakan metode verifikatif. Populasi dalam penelitian ini adalah semua pemerintah daerah Kabupaten dan kota Jawa Barat pada 2012-2017 dan diperoleh 162 sampel data penelitian yang terdiri dari 1 provinsi, 26 kabupaten dan kota. Teknik analisis data dalam kajian ini menggunakan analisis regresi berganda. Berdasarkan hasil analisis regresi menunjukkan bahwa laju pertumbuhan ekonomi kabupaten dan kota Se-provinsi Jawa barat dipengaruhi secara signifikan oleh pendapatan asli daerah (PAD), pendapatan transfer, pendapatan lain-lain yang sah, dan tingkat kemandirian daerah.Kata kunci : Pertumbuhan ekonomi; Pendapatan asli daerah; Pendapatan transfer; Lain-lain pendapatan yang sah; Tingkat kemandirian